PS01.056: ELECTRICAL STIMULATION OF THE LOWER ESOPHAGEAL SPHINCTER IN PATIENTS WITH GASTROESOPHAGEAL REFLUX DISEASE AND IMPAIRED ESOPHAGEAL MOTILITY. (14th September 2018) - Paireder, Matthias; Kristo, Ivan; Rieder, Erwin; Schwameis, Katrin; Steindl, Johannes; Schoppmann, Sebastian
Abstract: Background: Laparoscopic fundoplication (LF) is considered as standard surgical antireflux therapy. However, even if performed in specialized centers, the procedure can be followed by long-term side effects dysphagia, gas bloating or inability to belch. Especially patients with motility disorders (IEM) and concurrent GERD are prone to postoperative dysphagia after LF. The aim of this study is the evaluation of electrical stimulation (EST) of the lower esophageal sphincter (LES) in patients with IEM and GERD and its impact on procedure-related gastrointestinal side effects such as dysphagia. Methods: This is a prospective, open-label, non-randomized single-center study. All variables are depicted as median and interquartile range (IQR) or 95% confidence intervals (CIs) or mean with standard deviation (SD). Ineffective esophageal motility (IEM) was defined as a Distal Contractile Integral (DCI) below 450 mmHg-s-cm in ≥ 5 of out 10 swallows. Differences in GERD health-related quality of life (HRQL) scores before and after treatment were compared with paired t-test due to a normal distribution. P-values < 0.05 were considered significant. Results: Between 05/2015 and 10/2017 twenty patients were treated with LES-stimulation for GERD. Thirteen patients (61.9%) presented with IEM in esophageal manometry before surgery and were included in this analysis. DCI was 91 (IQR 30.5–331.5) mmHg-s-cm. Median 24-hours esophageal pH at baseline was 10.2% (IQR 4.4–21.5). Fifty-seven percent of patients were treated with PPI at time of surgery. Nine patients (69.2%) presented with typical GERD symptoms whereas 6 patients (46.2%) also presented with atypical GERD symptoms. BMI was 26.1 (SD 4.9). Eight patients (61.5%) showed a hiatal hernia at the time of surgery and underwent also hiatal repair. Operating time was 59 minutes (IQR 34.5–70.25). HRQL for heartburn at baseline was 21.1 (SD 5.4) and improved to 7.3 after surgery (SD 6.7) at follow up of one month (mean difference 13.8 (CI 12.5–15.1) P  < 0.001). HRQL for regurgitation at baseline was 18.69 (SD 6.9) and improved to 3.84 (SD 2.4) (mean difference 14.9 (CI 13.95–15.76) P  < 0.001). No patients showed any clinical signs of dysphagia nor impaired findings in postoperative contrast swallow. Gastrointestinal side effects such as the inability to belch or bloating were not seen in any patients. There were no severe adverse events related to the procedure, but one patient need re-do surgery and re-implantation of the LES-stimulation due to a breaking of the lead close to the implanted pulse generator after one year. Conclusion: LES-EST was introduced as a potential alternative technique to avoid side effects of LF. It was demonstrated that LES-EST significantly raises the LES pressure and improved GERD symptoms such as heartburn and regurgitation. The advantage of this procedure is that the anatomy of the esophageal-gastric junction is not altered dramatically. Disclosure: All authors have declared no conflicts of interest.